2017
DOI: 10.1093/jjco/hyx031
|View full text |Cite
|
Sign up to set email alerts
|

High expression of IRE1 in lung adenocarcinoma is associated with a lower rate of recurrence

Abstract: High expression of endoplasmic reticulum stress-related genes was observed in patients with lower stages of lung adenocarcinoma and minimal vascular invasion. High inositol-requiring kinase 1 expression was an independent predictor of recurrence-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Total RNA was extracted from cultured cells or patient tumor specimens and reverse transcribed into cDNA, as described previously ( 23 ). Quantitative real-time polymerase chain reaction (qRT-PCR) was performed using the following primers: glyceraldehyde 3-phosphate dehydrogenase (GAPDH), forward 5′-CAC CAC CAA CTG CTT AGC AC-3′ and reverse 5′-TGG CAG GTT TTC TAG ACG G-3′; GCLC, forward 5′-ACG GAG GAA CAA TGT CCG AG-3′ and reverse 5′-TAC TGA AGC GAG GGT GCT TG-3′; xCT, forward 5’-CAG GAG AAA GTG CAG CTG AA-3′ and reverse 5′-CTC CAA TGA TGG TGC CAA TG-3′; all CD44, forward 5′-TCG CTA CAG CAT CTC TCG GA-3′ and reverse 5′-TGC TGC ACA GAT GGA GTT GG-3′; and CD44v8-10, forward 5′-GAC AGA ATC CCT GCT ACC AAT A-3′ and reverse 5′-ATG TGT CTT GGT CTC CTG ATA A-3′.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Total RNA was extracted from cultured cells or patient tumor specimens and reverse transcribed into cDNA, as described previously ( 23 ). Quantitative real-time polymerase chain reaction (qRT-PCR) was performed using the following primers: glyceraldehyde 3-phosphate dehydrogenase (GAPDH), forward 5′-CAC CAC CAA CTG CTT AGC AC-3′ and reverse 5′-TGG CAG GTT TTC TAG ACG G-3′; GCLC, forward 5′-ACG GAG GAA CAA TGT CCG AG-3′ and reverse 5′-TAC TGA AGC GAG GGT GCT TG-3′; xCT, forward 5’-CAG GAG AAA GTG CAG CTG AA-3′ and reverse 5′-CTC CAA TGA TGG TGC CAA TG-3′; all CD44, forward 5′-TCG CTA CAG CAT CTC TCG GA-3′ and reverse 5′-TGC TGC ACA GAT GGA GTT GG-3′; and CD44v8-10, forward 5′-GAC AGA ATC CCT GCT ACC AAT A-3′ and reverse 5′-ATG TGT CTT GGT CTC CTG ATA A-3′.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“… 45 For instance, increased expression levels of major actors of the UPR such as IRE1α, unspliced and spliced XBP1, PERK and ATF6 were observed in tissues sections from a variety of human tumors including brain, breast, gastric, kidney, liver, lung and pancreatic cancers ( Table 1 ). 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 Moreover, the chaperone GRP78 is also found overexpressed in many cancers 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 and is involved in the dissemination/metastasis of human tumors. GRP78 overexpression is associated with higher tumor grades and reduced patients’ survival.…”
Section: Upr Molecular Mechanisms and Their Functions In Cancers: Thementioning
confidence: 99%
“…26 ERN2 also activates serine/threonine-protein kinase and participates in the response to EGFR-TKIs. 27,28 Our study observed that the expression of EEF1A2 was downregulated in patients with MLNM harboring EGFR 19Del mutations compared with those patients without MLNM, and conversely upregulated in patients with MLNM harboring EGFR L858R mutations, whereas the expression of ERN2 was upregulated in patients with EGFR 19Del mutations and downregulated in those with EGFR L858R mutations. The expression of ERN2 was verified with quantitative RT-PCR in these 10 patients and found to be consistent with the results from transcriptome sequencing.…”
Section: Discussionmentioning
confidence: 63%